The The Role of the Teenage Ta'lim Assembly in Establishing the Morality of Youth - Bahagia Bahagia; Rimun Wibowo; Siti Nurasiyah; Naskiyah Naskiyah (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
Taklim assembly is classified as an association outside of school to shape the morals of teenagers. This study aims to determine the effectiveness of the taklim assembly in shaping the morals of teenagers. At the same time to find the contribution of the taklim assembly in shaping the morals of youth. The research method used is descriptive qualitative approach. Determination of the sample as the object of research using a purposive technique. The results showed that the Majelis taklim was very effective in improving the morals of teenagers because the Majelis taklim as a forum or place for teenagers to gain knowledge about morals and worship in religion. Another finding is that the taklim assembly carries out various moral developments for adolescents starting from providing motivation to adolescents, developing quality youth resources such as teaching social morals according to Islamic teachings, inviting youth as administrators of the taklim assembly and carrying out religious counseling. At the same time providing an example or example for teenagers to follow the example of the teachers in the taklim assembly. In the economic field, youth have been involved in youth empowerment activities such as making dish soap, deodorizing clothes and vehicle lubricants.